2010
DOI: 10.1007/s12630-009-9241-4
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of the ProSeal™ laryngeal mask airway is more successful with the 90° rotation technique

Abstract: Purpose The 90°rotation technique for inserting the ProSeal TM laryngeal mask airway (PLMA) in anesthetized paralyzed patients was compared with the index finger insertion technique. Methods One hundred twenty Asian adult patients were randomly allocated to either a standard technique group or a rotation technique group. A PLMA size 4 was used for women and size 5 was used for men. In the standard technique group (n = 60), the PLMA was inserted using the index finger. In the rotation technique group (n = 60), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 17 publications
(18 reference statements)
1
49
0
Order By: Relevance
“…This success rate is consistent with previous reports, in which the primary success rate for i-gel insertion with the standard technique was 78-93% [8,10,17]. Our previous reports comparing two insertion techniques for the ProSeal LMA showed that the success rate at the first attempt was significantly higher in the rotation group than in the standard technique group [13][14][15], similar to the present study using the i-gel. Our findings suggest that the standard digital technique to insert supraglottic airway devices such as the i-gel or ProSeal LMA should be replaced with the rotational technique to increase the first-attempt insertion success rate.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This success rate is consistent with previous reports, in which the primary success rate for i-gel insertion with the standard technique was 78-93% [8,10,17]. Our previous reports comparing two insertion techniques for the ProSeal LMA showed that the success rate at the first attempt was significantly higher in the rotation group than in the standard technique group [13][14][15], similar to the present study using the i-gel. Our findings suggest that the standard digital technique to insert supraglottic airway devices such as the i-gel or ProSeal LMA should be replaced with the rotational technique to increase the first-attempt insertion success rate.…”
Section: Discussionsupporting
confidence: 93%
“…A recent case report showed that the reverse technique for i-gel insertion, with the device inserted into the mouth upside-down, may be useful to improve the insertion success rate when the first attempt by the standard technique fails [12]. Our previous studies demonstrated that the rotational technique provides a higher success rate at the first attempt with less pharyngeal mucosal trauma than the standard technique for insertion of the ProSeal TM laryngeal mask airway (LMA) [13][14][15]. To our knowledge, there have been no previous reports regarding the efficacy of the rotational technique for i-gel insertion.…”
Section: Introductionmentioning
confidence: 99%
“…Sample size: A previous study reported 17% higher success rate with the 90 degree rotation technique (19). Expecting a minimum difference of 17% in the success rate we chose a sample size of 60 patients per group.…”
Section: Discussionmentioning
confidence: 99%
“…The technique simply consists of insertion of the PLMA into the oral cavity, 90° rotation around the tongue and advancement (19). It may seem that rotating the large cuff inside the mouth may be difficult, but it is easy to insert PLMAs using the rotation insertion technique.…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to the previous study conducted by Hwang et al in 160 patients and Jeon et al in 120 patients. 9,14 It was observed that there were multiple attempts in standard technique. Four patients in ST group had two insertion attempts & nine patients had three insertion attempts.…”
Section: Discussionmentioning
confidence: 99%